Prostaglandin Analogous and Antioxidant Activity Mediated Gastroprotective Action of Tabernaemontana divaricata (L.) R. Br. Flower Methanolic Extract against Chemically Induced Gastric Ulcers in Rats. (29th October 2013) - Ali Khan, Mohammed Safwan; Mat Jais, Abdul Manan; Afreen, Adiba
Abstract : The present study was conducted to evaluate the antiulcerogenic effect and recognize the basic mechanism of action of Tabernaemontana divaricata (L.) R. Br. flowers. T. divaricata flower methanolic extract (TDFME) was screened for antiulcer activity versus aspirin and ethanol induced gastric ulcers at three doses—125, 250, and 500 mg/kg—orally using misoprostol as a standard. Besides histopathological examination, seven parameters, that is, ulcer index, total protein, nonprotein sulphhydryls, mucin, catalase, malondialdehyde, and superoxide dismutase levels, were estimated. In addition to HPLC profiling, GC-MS analysis and electrospray ionization—high resolution mass spectral (ESI-HRMS) analysis of crude TDFME were carried out in an attempt to identify known phytochemicals present in the extract on the basis of m/z value. The results revealed a significant increase in the levels of catalase, superoxide dismutase, mucin, and nonprotein sulphhydryls, while they revealed a reduction in ulcer index, the levels of total protein, and malondialdehyde. Histopathological observations also demonstrated the protective effect. Though all the doses of TDFME exhibited gastroprotective function, higher doses were found to be more effective. Mass spectral analysis gave a few characteristic m/z values suggesting the presence of a few known indole alkaloids, while HPLC profiling highlighted the complexity of the extract. TDFME was found to exhibit its gastroprotective effect through antioxidant mechanism and by enhancing the production of gastric mucous.